Logging While Drilling Via Autonomous Sonde - Kepic, Anton; Dupuis, Christian; Stewart, G.; Wilkinson, B.; Greenwood, Andrew; Podolska, Anna (EAGE, 2014)
We present a method of geophysical logging while tripping drill rods to produce logs similar to wireline logs. The process is autinmous in that it does not require any significant changes by the driller and does not require any modifications to the drill rig. Using starting depth, rod length, and sensors on the sonde a geophysical log can be created when the drill rods are retreived upon hole completion. Thus, this methodology is very suitable for slimhole and diamond drilling methods that do not case the completed hole. Such holes often collapse and are too expensive to log via wireline logging.